Multimodal analysis of TAAD pathogenesis: SHAP-enhanced interpretable models and single-cell sequencing analysis reveal immune microenvironment alterations - Wang, Zhong; Wang, Yixian; Tang, Dianjun; Gang, Qingwei; Shen, Shikai; Wei, Hongming; Zhao, Dongwen; Zhang, Jian (Frontiers in Immunology, 2026)
BackgroundStanford type A aortic dissection (TAAD) is a fatal cardiovascular emergency with high mortality within 48 hours. Elucidating molecular mechanisms and identifying reliable biomarkers are essential for improving diagnosis and guiding targeted interventions.MethodsWe integrated four transcriptome datasets and two single-cell transcriptomic datasets using Harmony batch correction. Differentially expressed genes were identified with DESeq2. Three machine learning algorithms, LASSO, random forest, and SVM-RFE, were employed to identify hub genes, and SHAP analysis was used to quantify their individual contributions. A diagnostic system incorporating seven algorithms was constructed. Immune infiltration profiling, cell-cell communication analysis, and pseudotime trajectory analysis were performed. The proliferation and migration of vascular smooth muscle cells (VSMCs) were assessed using CCK-8 and wound healing assays.ResultsIntegration of bulk and single cell transcriptomic datasets identified three hub genes, SIX4, SCNN1B, and PCDH11X, through convergent machine learning approaches. SHAP analysis highlighted SIX4 as the predominant predictor within diagnostic models, which consistently achieved high accuracy (AUC > 0.9). Single cell profiling localized SIX4 expression to synthetic vascular smooth muscle cells, where it was linked to enhanced CXCL12–CXCR4 mediated immune interactions and remodeling of the inflammatory microenvironment. Functional assays confirmed that SIX4 overexpression promoted vascular smooth muscle cell proliferation and migration, corroborating its role in TAAD progression.ConclusionThis study uncovered SIX4, SCNN1B, and PCDH11X as critical regulators of TAAD. SIX4 was identified as a key modulator of smooth muscle cell plasticity and immune signaling dynamics. These findings deepen our understanding of TAAD pathogenesis and demonstrate the utility of SHAP-guided models in identifying and prioritizing mechanistic drivers in this complex vascular disease.